2013
DOI: 10.1021/jf305076v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pomegranate Seed Oil on Glucose and Lipid Metabolism-Related Organs in Rats Fed an Obesogenic Diet

Abstract: Studies conducted in mice have revealed positive effects of punicic acid (PUA). The aim of this study was to analyze the effects of PUA on fat accumulation and glycemic control in rats fed an obesogenic diet. Rats were randomly divided into two groups: control group and PUA group (diet supplemented with 0.5% PUA). No changes were observed in adipose tissue weights. The glucose tolerance test showed that the glycemic value in the PUA group had decreased significantly at the final time (120 min) (-19.3%), as had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
(81 reference statements)
3
29
1
Order By: Relevance
“…A similar study was performed by Miranda et al That used diet with 0.5% PA in rats. The results of this study showed no changes in adipose tissue weights and insulin resistance, but the glycemic value in the PA group had decreased, significantly 77 . Improvement in insulin sensitivity is associated with reducing the risk of developing type 2diabetes.…”
Section: Effects On Insulin Resistancementioning
confidence: 54%
See 1 more Smart Citation
“…A similar study was performed by Miranda et al That used diet with 0.5% PA in rats. The results of this study showed no changes in adipose tissue weights and insulin resistance, but the glycemic value in the PA group had decreased, significantly 77 . Improvement in insulin sensitivity is associated with reducing the risk of developing type 2diabetes.…”
Section: Effects On Insulin Resistancementioning
confidence: 54%
“…An interesting result from this research was hypoplasia induced in the liver due to the anti-proliferative effect on hepatocytes increased transaminase levels. Also, this issue should be considered before proposing PA as a functional ingredient 77 . Another study performed by Yamasaki et al with diets containing 0%, 0.12%, or 1.2% PSO for 3 weeks, showed a meaningful increase in serum triacylglycerol and phospholipid levels but not in total cholesterol in the PSO treated groups 43 .…”
Section: Effects On Lipid Profilementioning
confidence: 99%
“…have shown PA did not decrease the fat accumulation in liver and other organs of rats fed an obesogenic diet and did not lead to improve glycemic control. [20] Nekooeian et al . investigated the impact of PSO Type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pomegranate oil in rat diets has been shown to significantly decrease glycemic values but not significant change fat accumulation in adipose tissue, liver, or skeletal muscles .…”
Section: Health Advantages Of Pomegranate Seed Oilmentioning
confidence: 98%